Model Pemungutan Suara Pada Pemilihan Umum 2024 Di Provinsi Papua Pegunungan - Yahuli, Rolin; Herning Sitabuana, Tundjung (Universitas Ekasakti, 2024)
General elections are an important part of a democratic country. Based on Article 22 E of the 1945 Constitution, general elections in Indonesia are held periodically (every 5 years) using the direct, general, free, secret, honest and fair principles. Voting takes place during the general election process, which each voter exercises their right to vote by coming to the local polling station and voting on the ballot paper. This kind of process cannot be carried out in all provinces in Indonesia, considering the different natural conditions. The purpose of this study is to identify the voting model in the 2024 general election in the Papua Mountain Province, whose natural conditions are located in a mountainous area that is difficult to reach by road. The method of analysis that the researchers used in this study was normative legal analysis, with descriptive applications used as a specific type of analysis. Secondary data, which includes primary, secondary, and tertiary legal material is the type of data that is used in this study. Researchers use data collection strategies from literature studies to get data, the data was analyzed thorugh the application of qualitative analytical methodologies. The outcomes demonstrated that the Papua Mountain Provinces is use the noken system as its voting model for the general election in 2024.